Low phase noise performance of VCO using MEMS - Al-Khateeb, Khalid A. Saeed; Mohd Subki, M. Mu’adz (2008)
The paper presents a monolithic voltage controlled oscillator (VCO) prototype designed with micro-electro-mechanical systems (MEMS) devices. It achieves the stringent performance requirements of various wireless communication applications such as GSM cellular telephony. The VCO meets the low phase noise requirement of -136 dBc/Hz at large offset frequency (3 MHz) over the appropriate frequency range. A model for the simulation of the monolithic VCO is proposed. A suitable topology for the model is the Colpitts oscillator. It is relatively less complicated, which facilitates the practical integration of the LC components. The main components in the configuration are the MEMS variable capacitor and monolithic 3-D coil inductor. These components are suitable for low phase-noise and low power consumption at the application frequencies.